Zakonska ureditev pravic pacientov de lege ferenda - Gerbec, Franc (Podjetje in delo, 2023)
The Republic of Slovenia has established laws, such as the Patients' Rights Act, to protect and promote the well-being of patients. These laws outline the mechanisms and methods for safeguarding patients' rights to healthcare, as well as the monetary and non-monetary benefits they are entitled to through compulsory health insurance. Several institutions are responsible for ensuring that patients' rights are upheld, including Patients' Rights Representatives, the Ombudsman, the Equality Ombudsperson, and the Commission of the Republic of Slovenia for the Protection of Patients' Rights. However, various data indicate a significant lack of implementation when it comes to patients' rights. Issues such as lengthy waiting times and waiting lists greatly impede timely, fair, high-quality, and safe healthcare. Furthermore, there is currently no regulatory framework in place to address the quality and safety of healthcare, as well as non-contractual liability for harm caused to patients. To overcome these challenges, it is proposed that substantial changes be made to the current regulation of patients' rights. One suggestion is the establishment of a Patients' Ombudsman and a National Council for the Protection of Patients' Rights. Additionally, management of waiting times and waiting lists must be reformed to ensure their reduction both at the healthcare providers' level and nationally.
Keywords: Bolnikove pravice; čakalne dobe; čakalni seznami; medicina; pacienti; pravo; zdravstvena obravnava; zdravstvo